ChemInform Abstract: Efficient Synthesis of 2‐Ureaguanines via the in situ Reactions of 2‐Isocyanatopurines with Amines. Issue 44 (14th October 2013) - Le Roux, Antoine; Marsault, Eric
Abstract 6, 9‐Diprotected guanines (I) are found to be suitable substrates for the synthesis of 2‐ureaguanines.